Integrasi Spiritualitas Islam, Entrepreneurial Traits, dan Resilience Capacity dalam Ketahanan Usaha Hortikultura - Abdul Latif; Elfira Yunita Sapitri; Subiyantoro Subiyantoro; Eni Hidayati; Baha Shofa Mijdal (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
This study was motivated by the high unemployment rate, which has a negative social impact. Entrepreneurship is one of solution to economic uncertainty, market fluctuations, and climate risks that affect business sustainability. These conditions require business resilience that is not only based on economic and managerial aspects, but also on the values and character of business actors. This study aims to analyze business survival power in Islamic entrepreneurship through the integration of Islamic spirituality, entrepreneurial character, and business resilience capacity at Syaqila Buah Trading Company. This study uses a qualitative approach with a case study design. Data were obtained through in-depth interviews, direct observation, and documentation, then analyzed using data condensation, data presentation, and conclusion drawing techniques. The results show that Islamic spirituality, such as zakat, tawakal, gratitude, trustworthiness, and honesty, serve as a foundation of values that guide decision-making and maintain the psychological stability of entrepreneurs. These values are integrated with entrepreneurial characteristics such as optimism, persistence, courage to take risks, proactivity, and innovation, thereby strengthening business resilience capacity as reflected in adaptability, operational flexibility, problem solving, business learning, and relational resilience. The research contribution shows an integrative model of horticultural business actors, viewing that resilience in entrepreneurship is formed not only through character and business resilience, but also spirituality as a core part of the entrepreneurial ecosystem.